التوجه الزمني لدى طلبة الجامعات الفلسطينية في محافظة طولكرم - بركات, زياد (جامعة الوادي - University of Eloued, 2018)
هدفت الدراسة التعرف إلى مستوى التوجه الزمني لدى طلبة الجامعات الفلسطينية في محافظة طولكرم في ضوء متغيرات: الجنس، والمستوى التحصلي. والجامعة، والتخصص، وتكونت عينة الدراسة من (423) طالباً وطالباً، اختيروا بطريقة العينة العشوائية الطبقية بنسبة (5%) من المجتمع تبعاً إلى متغيري الجنس والجامعة. أظهرت النتائج أن تقديرات أفراد الدراسة لمستوى التوجه الزمني الكلي كان متوسطاً، كما كانت هذه التقديرات متوسطة على التوجه الزمني الماضي والحاضر بينما كانت مرتفعة على التوجه الزمني المستقبلي. ومن جهة أخرى، أظهرت النتائج عدم وجود فروق دالة إحصائياً بين متوسطات تقديرات أفراد الدراسة لمستوى التوجه الزمني الكلي والمجالات الفرعية: الماضي والحاضر والمستقبل تبعاً إلى المتغيرات: الجنس، والتحصيل، والجامعة، والتخصص. وفي ضوء هذه النتائج ومناقشتها تم اقتراح عدة توصيات أهمها: حث الباحثين على إجراء دراسات مماثلة على مجتمعات وعينات أخرى مختلفة، وإجراء دراسات مرتبطة بالتوجه الزمني في علاقته بمتغيرات نفسية تربوية مختلفة.Abstract: The study aimed to identify the level of time orientation among Palestinian university students in Tulkarem governorate in light of variables: Gender, achievement level, university and specialization. The study sample consisted of (423) male and female students who were selected in the random stratified sample by(5%) of the society according to the sex and the university variables. The results showed that the members' estimates of the total time trend level were average, and these estimates were moderate to the past and present time, while high on the future time trend. On the other hand, the results showed that there were no statistically differences significant between the average of the Study members estimates of the total time trend and the subfields: past, present and future according to variables: gender, achievement, university and specialization. In light of these findings and their discussion, several recommendations have been proposed. The most important recommendations are: to urge researchers to conduct similar studies on different communities and samples, and to conduct time-related studies in relation to different psychological educational variables.
مقال
Keywords: التوجه الزمني، الماضي، والحاضر، والمستقبل; time orientation; past; present; future.